Edukasi Pemakaian Masker yang Benar dan Pencegahan COVID-19 di Desa Dajan Peken - Pratiwi, Ni Made Sintha; Apriani, Desak Gede Yenny; Putri, Desak Made Firsia Sastra; Dewi, Putu Adi Cahya; Astuti, Ni Luh Seri (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2021)
Coronavirus Disease 2019 (COVID-19) is a new type of disease that has never been previously identified in humans. The virus that causes COVID-19 is called SarsCoV-2. Common signs and symptoms of COVID-19 infection include symptoms of acute respiratory distress such as fever, cough, and shortness of breath. The average incubation period is 5-6 days, with the most prolonged incubation period being 14 days. In severe cases of COVID-19, it can cause pneumonia, acute respiratory syndrome, kidney failure, and even death. The increase in coronavirus cases in Indonesia shows that people still do not understand the dangers of coronavirus and how to prevent it. On the streets, It can be seen that there are still people who do not use masks and heed the recommendations for maintaining a safe distance. In Dajan Peken Village, it was found that many people did not comply with health protocols, and the public tended to be at risk of contracting COVID-19 due to the lack of public awareness of using masks when gathering in public places. Currently, people rarely spray disinfectant in their home environment, and physical distancing behavior in the community is still lacking. The purpose of this activity is to provide education about preventing COVID-19 and how to wear masks correctly. The measurement results showed that most public knowledge before being given health education was in the excellent category. The majority of general knowledge after being given health education was in the high class. The results show differences in public expertise before and after providing health education to prevent COVID-19 and how to wear masks correctly.ABSTRAKCoronavirus Disease 2019 (COVID-19) adalah penyakit jenis baru yang belum pernah diidentifikasi sebelumnya pada manusia. Virus penyebab COVID-19 ini dinamakan SarsCoV-2. Tanda dan gejala umum infeksi COVID-19 antara lain gejala gangguan pernapasan akut seperti demam, batuk dan sesak napas. Masa inkubasi rata-rata 5-6 hari dengan masa inkubasi terpanjang 14 hari. Pada kasus COVID-19 yang berat dapat menyebabkan pneumonia, sindrom pernapasan akut, gagal ginjal, dan bahkan kematian. Terjadinya peningkatan kasus virus corona di Indonesia menunjukkan bahwa masih ada masyarakat yang belum memahami bahaya virus corona dan bagaimana cara pencegahannya. Hal ini terlihat di jalan-jalan masih ada masyarakat yang tidak menggunakan masker dan mengindahkan anjuran jaga jarak aman. Di Desa Dajan Peken, ditemukan banyak masyarakat yang kurang mematuhi protokol kesehatan serta masyarakat cenderung berisiko tertular COVID-19 karena kurangnya kesadaran masyarakat menggunakan masker saat berkumpul ditempat umum. Saat ini masyarakat sudah jarang menyemprotkan desinfektan dilingkungan rumah, serta perilaku physical distancing pada masyarakat masih kurang. Tujuan kegiatan ini dalam rangka memberikan edukasi tentang pencegahan COVID-19 dan cara memakai masker yang benar. Hasil pengukuran didapatkan hasil mayoritas pengetahuan masyarakat sebelum diberikan pendidikan kesehatan yaitu berada pada kategori cukup, dan mayoritas pengetahuan masyarakat setelah diberikan pendidikan kesehatan yaitu berada pada kategori tinggi. Hal ini menunjukkan bahwa ada perbedaaan pengetahuan masyarakat sebelum dan sesudah pemberian pendidikan kesehatan pencegahan COVID-19 dan cara memakai masker yang benar.